DETECTION OF blaCTX-M AND blaSHV GENES OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING Klebsiella pneumoniae - ZAHOOR , S; SAGHEER , S; ANWAR , R; MAHMOOD , S; PARA , M; TABASSUM , I; MUGHAL , VA (Biological and Clinical Sciences Research Journal, 2024)
Antimicrobial resistance poses a significant challenge in many hospitals, increasing infection morbidity and mortality. It is a global issue with far-reaching implications for human and animal health, the environment, agriculture, and the economy. The ineffective use of antibiotics in treating infectious diseases is a significant driver of antimicrobial resistance, which can be either innate or acquired.Objective: This study aimed to detect the presence of blaCTX-M and blaSHV genes in extended-spectrum beta-lactamase (ESBL) producing Klebsiella pneumoniae and to evaluate the antibacterial activity of zinc oxide (ZnO) nanoparticles synthesised using Calotropis procera extract. Methods: A cross-sectional study was conducted at Lahore College for Women University, Lahore, from January to December 2023. A total of 20 clinical isolates of Klebsiella pneumoniae were collected and identified using standard microbiological techniques. The presence of ESBL-producing strains was detected using the double disc synergy test. Polymerase chain reaction (PCR) was used to detect blaCTX-M and blaSHV genes. ZnO nanoparticles were synthesised using Calotropis procera extract and tested for antibacterial activity against ESBL-producing strains at different concentrations (20 mg/ml, 25 mg/ml, 30 mg/ml, and 35 mg/ml). The antibacterial activity was evaluated using the disc diffusion method, and data were analysed using SPSS version 23.0. Results: Of 20 clinical isolates, 15 (75%) were ESBL positive, and 5 (25%) were ESBL negative. PCR results showed that 80% of the ESBL-producing strains contained the blaCTX-M gene, and 83% included the blaSHV gene. The antibacterial activity of ZnO nanoparticles was concentration-dependent, with the highest inhibitory zones observed at a concentration of 35 mg/ml. The synergistic effect of ZnO nanoparticles with cefotaxime and ceftriaxone significantly increased the antibacterial activity against ESBL-producing strains. Conclusion: The study highlights the significant presence of blaCTX-M and blaSHV genes in ESBL-producing Klebsiella pneumoniae. The green synthesis of ZnO nanoparticles using Calotropis procera extract demonstrated enhanced antibacterial activity, especially when combined with beta-lactam antibiotics. These findings suggest that ZnO nanoparticles could be an alternative strategy to combat antimicrobial resistance.